Growth patterns of noetiid ligaments: implications of developmental models for the origin of an evolutionary novelty among arcoid bivalves - Thomas, R; Madzvamuse, A; Maini, P; Wathen, A (2000)
The dorsal ligaments of arcoid bivalves typically consist of oblique, lamellar and fibrous sheets, alternating along the hinge so that their attachments form characteristic chevron patterns. New elements are added at or near the middle of the pattern, as the ligament grows ventrally and gets longer. Most Palaeozoic arcoids exhibit this growth pattern, which still predominates among their living descendants. Early in the Cretaceous, a novel pattern emerged, with vertical strips of lamellar ligament embedded in grooves in the sheet of fibrous ligament which is attached to each valve. In contrast with the chevron, duplivincular ligament, new elements are added to each end of the noetiid ligament, anteriorly and posteriorly. This distinctive growth pattern is the defining character of the family Noetiidae. Remarkable variation among individuals within populations of a living limopsid arcoid includes Forms with vertical strips of lamellar ligament. These variants suggest how the noetiid growth pattern could have been derived from the duplivincular pattern. Computer simulations show that such patterns can be generated by a reaction-diffusion mechanism of the sort first conceived by Turing (1952, Philosophical Transactions of the Royal Society London, Series B, 237, 37-72). Moreover. the noetiid growth pattern can simply be derived from the duplivincular pattern by a developmental switch based, for example, on a change in boundary conditions. These results indicate that striking differences in form may arise from modest changes in the developmental process. The evolution of the Noetiidae, members of which are quite disparate in overall shell form, should be reassessed. The derived character on which this Family is based may nor be uniquely shared, so the group could well be polyphyletic.